2017
DOI: 10.1038/s41598-017-13395-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between pulse wave velocity and hot flashes/sweats in middle-aged women

Abstract: As women age and go through menopause, they suffer a higher incidence of cardiovascular morbidity and mortality. Previous studies have shown that a relationship exists between hot flashes/sweats and an increased risk of cardiovascular disease. However, the association between hot flashes/sweats and arterial stiffness is unclear. We aim to explore the relationship between hot flashes/sweats and arterial stiffness using the modified Kupperman index (KMI) questionnaire and measure the brachial-ankle pulse wave ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… 33 In addition, a recent analysis of data from The Women’s Health Initiative CaD study revealed that the number of menopausal symptoms (≥2 menopausal symptoms vs. none) is associated with a higher occurrence of cardiovascular disease (aHR 1.35, 95% CI 1.18–1.54). 34 The menopausal VMS has been reported to be associated with vascular risk factors such as hypertension, 35 diabetes, 36 and dyslipidemia, 37 and also with arterial stiffness, 38 39 endothelial dysfunction, 39 and proinflammatory cytokines such as interleukin-8 and tumor necrosis factor alpha. 40 Moreover, migraine was reported to be associated with an increased risk of hypertension in menopausal females based on data from a large French cohort (aHR 1.29, 95% CI 1.24–1.35).…”
Section: Discussionmentioning
confidence: 99%
“… 33 In addition, a recent analysis of data from The Women’s Health Initiative CaD study revealed that the number of menopausal symptoms (≥2 menopausal symptoms vs. none) is associated with a higher occurrence of cardiovascular disease (aHR 1.35, 95% CI 1.18–1.54). 34 The menopausal VMS has been reported to be associated with vascular risk factors such as hypertension, 35 diabetes, 36 and dyslipidemia, 37 and also with arterial stiffness, 38 39 endothelial dysfunction, 39 and proinflammatory cytokines such as interleukin-8 and tumor necrosis factor alpha. 40 Moreover, migraine was reported to be associated with an increased risk of hypertension in menopausal females based on data from a large French cohort (aHR 1.29, 95% CI 1.24–1.35).…”
Section: Discussionmentioning
confidence: 99%
“…However, this protection diminishes after menopause, with dramatic increases in arterial stiffening in the years following menopause onset [30–32]. Importantly, more severe symptoms in menopause are associated with greater arterial stiffness, and the association between mortality and arterial stiffness in females is double that in males [32,33]. In our own study of Tanzanian women, years since menopause onset was also associated with higher PWV, even after controlling for age.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Furthermore, severe symptoms in menopause are associated with remarkable arterial stiffness, and the association between mortality and arterial stiffness in females is double that in males. [29] Thus, menopause should be considered when evaluating the association between UHR and arterial stiffness.…”
Section: Exposurementioning
confidence: 99%